VD_FINDINFO Décision / 2015 / 252 vom 23. März 2015 - VD Tribunal cantonal (2015)
FICTION DE LA NOTIFICATION, OPPOSITION TARDIVE, PRINCIPE DE LA BONNE FOI | 354 CPP (CH), 85 al. 4 CPP (CH), 90 CPP (CH)